2018
DOI: 10.1016/j.jtos.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mustard-induced corneal injury involves the sphingomyelin-ceramide pathway

Abstract: NM induces concentration- and exposure time-dependent damage to the cornea that increases in severity over time. Alterations in the sphingomyelin-ceramide pathway may contribute to the damaging effects of NM exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…DSBs, in particular, cause cell cycle arrest, genome stability, and chromosomal damage [ 7 ]. NM exposure in ex vivo and in vivo rabbit corneal injury models promoted apoptosis, epithelial–stromal separation, corneal collagen degradation, and neovascularization [ 3 , 5 , 8 , 9 , 10 ]. Earlier studies using the murine skin injury model and rabbit corneal culture model demonstrated that exposure to the vesicating chemical agents sulfur mustard (SM) and nitrogen mustard (NM) exposure led to increases in apoptotic cell death and epidermal thickness and biomarkers, such as COX2 (cyclooxygenase 2, mediation of inflammation), MMP-9 (matrix metalloproteinase-9, inflammatory marker), and VEGF (vascular endothelial growth factor, angiogenic factor) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…DSBs, in particular, cause cell cycle arrest, genome stability, and chromosomal damage [ 7 ]. NM exposure in ex vivo and in vivo rabbit corneal injury models promoted apoptosis, epithelial–stromal separation, corneal collagen degradation, and neovascularization [ 3 , 5 , 8 , 9 , 10 ]. Earlier studies using the murine skin injury model and rabbit corneal culture model demonstrated that exposure to the vesicating chemical agents sulfur mustard (SM) and nitrogen mustard (NM) exposure led to increases in apoptotic cell death and epidermal thickness and biomarkers, such as COX2 (cyclooxygenase 2, mediation of inflammation), MMP-9 (matrix metalloproteinase-9, inflammatory marker), and VEGF (vascular endothelial growth factor, angiogenic factor) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While one ocular corrosive (tetraethylene glycol diacrylate) showed almost no measurable response at 3 h, there was almost complete loss of stromal cell viability as measured by the ability to maintain actin, an ATP-dependent process, at 24 h. This material is a DNA cross-linker and may act as a fixative (Mabilleau et al, 2006). Previous studies of nitrogen mustards have identified a similar delay in cellular damage associated with DNA cross-linking (Charkoftaki et al, 2018). Similar delayed injury was noted in live animal studies for other cross-linking materials such as aldehydes (Maurer et al, 2001b) as well as bleaches (Maurer et al, 2001a).…”
Section: Discussionmentioning
confidence: 86%
“…cause several corneal abnormalities [ 31 , 33 , 116 , 117 ]. Various ocular pathologies such as ocular edema, redness, tearing, itching, abrasion, corrosions, corneal injury, neovascularization, blurred vision, and loss of vision in humans and animals have been observed following exposure to industrial chemicals (alkali, acids, anhydrous ammonia, phosphine), warfare agents (mustard gas, chlorine, acrolein, phosgene oxime, lewisite) and pesticides (carbofuran, ethylene oxide) [ 32 , 33 , 35 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Our recent studies and research reported in the literature have led us to postulate that irregular autophagosomal and lysosomal biogenesis leads to improper clearance of injurious factors and the accumulation of unwanted and harmful molecules/proteins in keratocytes, ultimately resulting in corneal pathologies.…”
Section: Dysregulated or Delayed Autophagy And Its Late Effectsmentioning
confidence: 99%